Plan de negocios para la creación de una empresa productora y comercializadora de derivados ovinos en la provincia de Chimborazo - Guerrero Alvarado, Kenneth Alberto (2021)
In the first chapter, different points were elaborated such as the problem found in the sector or opportunities and what are the justifications that defend the present project so that the business plan has the expected performance. Therefore, the theoretical bases by which the research is supported to use the correct methodology and to be able to define the different points as legal, conceptual, investigative were established……….